LAY CONCEPTUALIZATIONS OF FORGIVENESS AMONG PORTUGUESE ADULTS: A PROVERB ENDORSEMENT APPROACH - Neto, Félix; Mullet, Etienne (Proverbium - Yearbook, 2011)
Lay conceptualizations about forgiveness were examined using a proverb endorsement approach. Three hundred and three participants living in Portugal were presented with 40 proverbs related to forgiveness, and instructed to assess the degree to which they agree with their content. Trough exploratory and confirmatory factor analyses, four conceptualization factors were found: Positive aspects of forgiveness, Negative aspects of forgiveness, Forgetting is not forgiving, and Forgiveness as moral revenge. Several of these factors had already been found in previous studies but the Forgetting is not forgiving factor nicely complements the series of four conceptualization factors that comprise the Conceptualization of forgiveness model.